Theory of Planned Behaviour Untuk Menganalisis Perilaku Perawat dalam Pengembangan Berkelanjutan Keprofesian Keperawatan (Continuing Professional Development) - Neny Rif’ah; Sandra Dewi; Rina Anindita (Jurnal Health Sains, 2022)
Continuing Professional Development (CPD) for nurses is carried out in order to maintain and improve the competence of nurses so that they can continue to carry out process-oriented tasks and patient safety. The purpose of this study was to analyze the effect of nurses' beliefs about the importance of learning activities in the workplace, and the work environment on the behavior of nurses in continuing professional development of nursing at the Port Medical Center Hospital through nurses' motivation as an intervening variable. The research concept uses the Theory of Planned Behavior. Methods: This research method uses a quantitative approach with a causality design based on cross-sectional time dimensions. The population in this study used 60 nurses as a saturated sample. The analysis technique was using a questionnaire and tested using path analysis Results: There is a positive influence between Nurse Beliefs About the Importance of Learning Activities in the Workplace and Work Environment on Nurse Behavior in Nursing Professional Continuing Development (Continuing Professional Development) at Port Medical Center Hospital Through Nurse Motivation as an Intervening Variable. Implications: This research helps hospital management, especially the Education and Training section to develop an effective and efficient learning system, especially learning in the workplace such as the clinical afternoon program which is held once a week for 30 minutes to refresh knowledge about disease or medical action.